1-hour post-load plasma glucose: a reliable marker of insulin resistance in type 2 diabetes, as determined by the TyG index - Guo, Qingyu; Lv, Li; Yang, Xinyi; Chen, Min; Chen, Chen; Chen, Ting; Xu, Lili; Shen, Qiuyue; Gu, Ping; Shao, Jiaqing (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to investigate the correlation between 1-hour postprandial glucose (1h-PG) and the triglyceride-glucose (TyG) index in type 2 diabetes mellitus (T2DM) subjects and to evaluate the predictive utility of 1h-PG for insulin resistance (IR).Research design and methodsBased on the criteria of 1h-PG ≥ 8.6mmol/L and 2h-PG ≥ 11.1mmol/L from the 125-gram standard steamed buns meal test, 1835 T2DM individuals were categorized as follows: Group 1: 1h-PG < 8.6mmol/L; Group 2: 1h-PG ≥ 8.6mmol/L and 2h-PG < 11.1mmol/L; Group 3: 1h-PG ≥ 8.6mmol/L and 2h-PG ≥ 11.1mmol/L. The severity of IR was assessed using the TyG index, with thresholds of > 8.81 for males and > 8.73 for females. Clinical and laboratory parameters, including glucose, C-peptide, insulin and lipid profiles were analyzed. Statistical analyses included Spearman’s correlation, logistic regression, and receiver operating characteristic (ROC) curve analysis.Results1h-PG exhibited a more pronounced positive correlation with the TyG index (r = 0.273) than 2h-PG (r = 0.173). A statistically significant increase in the TyG index was observed in Group 2 compared with Group 1. Although Group 3 showed a trend toward a higher TyG index compared to Group 2, the difference was not statistically significant. The higher insulin resistance group exhibited significantly higher 1h-PG levels compared to the lower insulin resistance group. Logistic regression confirmed that the association between 1h-PG and the TyG index was stronger (OR = 1.170, 95% CI: 1.133–1.209, P < 0.001) than that of 2h-PG (OR = 1.091, 95% CI: 1.062–1.121, P < 0.001). ROC analysis revealed that 1h-PG achieved a higher AUC for predicting IR than 2h-PG (0.629 vs. 0.589, P < 0.0001).ConclusionAmong T2DM subjects, 1h-PG shows a stronger association with the TyG index than 2h-PG. These findings support the potential of 1h-PG as a more sensitive and cost-effective marker for early identification of insulin resistance, offering clinical utility in diabetes diagnosis and management.